(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The emergence of Cloud Computing and its constituent tools and technologies have found profound relevance and are the prime force of success in any business sector. The adaption and operations of Cloud Computing technologies in the educational sector is still at a slower pace in comparison to others. The paper aims to highlight the importance of applying Cloud Computing technologies to various aspects of the education sector and primarily focuses on three specific target users namely students, teachers and the organization as a whole. Over the years, the education industry has come a long way. Teaching and learning are no longer confined to textbooks and classrooms and now reaches computers and mobile devices. Today, learners are always connected — whether they are on or off school grounds. At the same time, the right technologies like cloud computing empower them with real-world and career- ready skills. Technology plays a massive role in this disruptive change.